The Comparison Study of Accounting Standards: Implementation On Phar-maceutical Company - Sigit Handoyo (Jurnal Akuntansi dan Auditing Indonesia)
Difference on characteristics in various countries will influence the implementation of accounting standard. Such conditions may include economic, social, cultural, and political condi-tions. As there are differences of accounting standard between one country and another, there also will be dissimilarities of financial reporting disclosure. Consequently, different accounting standard implementation will cause barriers to the users of financial report from a company, par-ticularly multinational enterprises, in foreign country. This article will analyse some differences in some posts as the result of unalike implementation of accounting standard, which will influence the number of rupiahs and dollars presented in the financial report. The samples of the research are four well-known pharmacy companies from four different countries namely Boehringer Ingel-heim in Germany, Pfizer in United States of America, CSL Ltd. in Australia, and PT. Kalbe Farma Tbk. in Indonesia. Those samples represent the implementation of four different reporting standard i.e. HGB (Handelsgesetzbuch), US GAAP, IFRS, and PSAK. Furthermore, this study will discuss the possibility of implementing harmonization as the consequence of difficulties faced by the users of financial report in comparing company performance caused by dissimilarities of ac-counting standard in those countries.